Anthropogenic factors influencing invasive ascidian establishment in natural environments. (October 2017) - Gewing, Mey-Tal; López-Legentil, Susanna; Shenkar, Noa
Abstract: Marine environments are constantly impacted by bioinvasions. Invasive ascidians (Chordata, Tunicata) are well-known for their ability to rapidly overgrow any available substrate. While the majority of studies have investigated the factors contributing to the successful establishment of ascidians on artificial substrates, the anthropogenic factors that contribute to such establishment on natural substrates have rarely been investigated. Here, we studied non-indigenous ascidians presence on natural substrate for the first time, using underwater field surveys at eight natural sites along the Israeli Mediterranean coast, in order to provide an analysis of factors assisting their establishment. The findings revealed that sites exposed to extended sewage-spill events experimented a reduction in native ascidian species. Understanding which factors alter ascidian population is essential for further monitoring efforts, to protect areas that are more susceptible to invasion, and for developing effective management tools to control further spread of invasive species in natural environments. Highlights: Underwater ascidian surveys were conducted at eight natural Mediterranean sites. We characterized natural habitats that are prone to invasive ascidians establishment. Our findings contribute to assessing where invasive ascidians will thrive. Sewage spill events had a negative effect on native species richness.